Implementasi Horisontal Net Untuk Meningkatkan Peran Perempuan Dalam Pengelolaan Kebun Bibit Rumput Laut - Kasim, Ma'ruf; Sudia, LaBaco; Nurdiana, Nurdiana; Jalil, Wardha (Universitas Mataram, 2024)
Seaweed cultivation currently uses the longline method. In practice, the longline method demands significant effort, leading to a greater male dominance in the cultivation process. This community service activity offers the most effective approach to enhancing the involvement of women in seaweed cultivation. We carried out this community service activity in one of the cultivation areas in North Buton Regency, Southeast Sulawesi Province. Seaweed farmers received training and assistance to implement horizontal nets. Twenty female seaweed farmers and 20 male farmers participated in the training. During the training activities, women play a significant role by performing practical tasks such as creating, cultivating, and maintaining horizontal net tools used in seaweed cultivation. At the field implementation level, women play a greater role in operating and maintaining horizontal nets. This community service activity has instilled new hope in expanding the availability of seaweed seed gardens and enhancing the role of women, thereby potentially increasing the income of female seaweed farmers.